Understanding the form and function in Chinese bound foot from last-generation cases - Mei, Qichang; Gu, Yaodong; Kim, Julie; Xiang, Liangliang; Shim, Vickie; Fernandez, Justin (Frontiers in Physiology, 2023)
Purpose: Foot adaptation in the typically developed foot is well explored. In this study, we aimed to explore the form and function in an atypical foot, the Chinese Bound foot, which had a history of over a thousand years but not practiced anymore. Methods: We evaluated the foot shape and posture via a statistical shape modelling analysis, gait plantar loading distribution via gait analysis and bone density adaptation via implementing Finite Element simulation and bone remodeling prediction. Results: The atypical foot with binding practice led to increased foot arch and vertically oriented calcaneus with larger size at the articulation, apart from smaller metatarsals compared with typically developed foot. This shape change causes the tibia, which typically acts as a load transfer beam and shock absorber to extend its function all the way through the talus to the calcaneus. This is evident in the bound foot by (i) reduced center of pressure trajectory in the medial-lateral direction, suggesting a reduced supination-pronation; (ii) increased density and stress in the talus-calcaneus articulation; and (iii) increased bone growth in the bound foot at articulation joints in the tibia, talus, and calcaneus. Conclusion: Knowledge from the last-generation bound foot cases may provide insights into the understanding of bone resorption and adaptation in response to different loading profiles.